Literature Study on the Impact of Micronutrient Deficiencies on Early Childhood Development - Firayani, Firayani (Pt. Anagata Sembagi Education, 2025)
Early childhood is a golden period in human life that greatly determines the quality of long-term growth and development. One important factor that supports the optimization of this phase is the fulfillment of micronutrient needs such as iron, iodine, zinc, and vitamin A. This study aims to examine in depth the impact of micronutrient deficiencies on early childhood development through a literature study method with a qualitative approach. The results of the literature search indicate that micronutrient deficiencies have a serious impact on cognitive development, physical growth, social-emotional abilities, and children's immune systems. Iron deficiency anemia, iodine deficiency, zinc deficiency, and lack of vitamin A have been shown to contribute to decreased IQ, motor delays, and increased risk of infectious diseases and child mortality. These findings emphasize that the problem of micronutrient deficiencies is a multidimensional issue that requires cross-sector interventions based on scientific evidence. These interventions include family education, fortification programs, and community empowerment in providing nutritious food. Thus, the fulfillment of micronutrients from an early age is a strategic step in developing superior, healthy, and productive human resources in the future